Malaysian nursing students' satisfaction with structured online learning - Romli, Muhammad Hibatullah; Wan Yunus, Farahiyah; Foong, Chan Choong; Soh, Kim Lam (Taylor & Francis Group, 2023)
The use of full online learning is projected to continue indefinitely. An instructional design for online learning that incorporates didactic, active learning activities, and health welfare is proposed. A single-subject multiple baseline design with two controls and two experiments was implemented with a class of 30 nursing students. Four weeks of online teaching alternates between control (e.g., didactic lecture with multimedia use) and experiment (e.g. adding active learning activities and health well-being education) phases. The students’ satisfaction was assessed using the Student Satisfaction with Online Learning questionnaire every week. Visual analysis of the plot graph showed that the experiments had higher satisfaction levels when compared with the controls. Statistically significant differences were found between student satisfaction levels in the control and experiment phases but not between the control phase and the experiment phase. Learners are more satisfied when online learning is well-planned and incorporates various learning activities.